Connecting the city: A three-dimensional pedestrian network of Hong Kong. (January 2021) - Sun, Guibo; Webster, Chris; Zhang, Xiaohu
The purpose of the paper is to investigate how a three-dimensional pedestrian network reshapes connectivity and helps to integrate the built environment of high-density cities. Using the case of Hong Kong, first, we elaborate how a continuous three-dimensional network constitutes an entirely different urban morphological spatial hierarchy compared to two-dimensional because of the footbridge system, underground connected with metro stations, and paths connected with mall developments. Second, we construct a three-dimensional pedestrian network model classifying segments into 23 categories with multi-height levels (e.g. sidewalk, footbridge, underground, crosswalk, ramp, paths on the building roof). Then we map the three-dimensional network for Hong Kong territory in a geographic information system, finding that the three-dimensional pedestrian network is 2.4 times in length and 8.5 times in link size greater than the road network. Connectivity comparison through a betweenness measure found striking differences between the two networks and indicated that footbridges and underground links could enhance walkability when they are well connected with the ground-level networks. Since road networks are widely used as a proxy for pedestrian analysis, we suggest that active travel optimisation planning, especially in high-density cities, requires a bespoke three-dimensional pedestrian model. The three-dimensional pedestrian network, enabling multi-level city living in a vertical metropolis, is a fundamental consideration in urban planning and design practices for high-density cities.